2012
DOI: 10.1016/j.atherosclerosis.2012.04.001
|View full text |Cite
|
Sign up to set email alerts
|

RAGE signaling mediates post-injury arterial neointima formation by suppression of liver kinase B1 and AMPK activity

Abstract: Objective Intima formation involves smooth muscle cell (SMC) proliferation and migration that ultimately drives arterial stenosis, thrombosis, and ischemia in atherosclerosis, hypertension, and arterial revascularization. Receptor for advanced glycation endproducts (RAGE) is a transmembrane signaling receptor implicated in diabetic renal and vascular complications, and post-injury intima formation, partly via Signal transducer and activator of transcription 3 (STAT3) activation. The metabolic super-regulator A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 30 publications
(35 reference statements)
1
25
0
1
Order By: Relevance
“…The results also indicate that by negatively regulating STAT3 phosphorylation through increased activation of AMPK, metformin inhibits monocyte-to-macrophage differentiation. Activation of STAT3 signaling is essential for neointima formation in vivo in response to carotid artery angioplasty (15). Metformin-and AICAR-activated AMPK was shown to inhibit proinflammatory gene expression in human liver cells by repressing IL-6-stimulated STAT3 phosphorylation (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also indicate that by negatively regulating STAT3 phosphorylation through increased activation of AMPK, metformin inhibits monocyte-to-macrophage differentiation. Activation of STAT3 signaling is essential for neointima formation in vivo in response to carotid artery angioplasty (15). Metformin-and AICAR-activated AMPK was shown to inhibit proinflammatory gene expression in human liver cells by repressing IL-6-stimulated STAT3 phosphorylation (24).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the AMPK signaling pathway suppresses proinflammatory responses and promotes macrophage polarization to an anti-inflammatory functional phenotype in macrophages (14). In addition, decreased AMPK activity with increased STAT3 in smooth muscle cells has been shown to promote receptor for advanced glycation end product signaling-induced neointima formation in response to arterial injury (15).…”
mentioning
confidence: 99%
“…In vascular smooth muscle cells, RAGE activation by AGE enhanced proliferation and migration by suppressing AMP-kinase activation [281]. Lander et al showed that AGE treatment of rat pulmonary artery smooth muscle cells caused activation of p21(ras) and NF-κB in a RAGE-dependent manner [282].…”
Section: Age-rage Signaling In Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…Left carotid artery ligation was performed as described (16), in 7-8 weeks old mice. Carotid arteries in euthanized animals were fixed with 4% paraformaldehyde (PFA) in PBS for morphological analysis or frozen for protein extraction and analysis by tissue SDS-PAGE Western blot.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, ENPP1 deficiency is associated with decreased soluble RAGE production by VSMCs and increased expression of the RAGE ligand S100A11 in vitro , and RAGE knockout inhibits AMC in Enpp1 −/− mice (14). RAGE is an essential mediator of injury-induced neointimal hyperplasia (15,16). RAGE ligand-induced signaling stimulates dysregulated ER stress responses (17), one of multiple inflammatory mechanisms by which RAGE signaling can promote diabetic organ complications.…”
Section: Introductionmentioning
confidence: 99%